1998
DOI: 10.1017/s0022029997002604
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour activity of yogurt: study of possible immune mechanisms

Abstract: The effect of yogurt on the inhibition of colon tumours induced by 1,2-dimethylhydrazine in BALB/c mice has been studied, and the hypothesis examined that yogurt induces a great reduction in the inflammatory immune response and inhibits tumour growth. Mice were assigned to five experimental groups: a control group fed with a conventional balanced diet, and four other test groups that received yogurt supplements for 2, 5, 7 or 10 consecutive days. At the end of each feeding period, mice were given su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 1 publication
3
37
0
1
Order By: Relevance
“…We observed that yoghurt supplements every 10 days for 6 months inhibited tumour development. We suggested that one of the mechanisms by which yoghurt exerts antitumour activity is through its immunomodulatory response mediated by a severe reduction (down regulation) of the inflammatory response induced by the carcinogen (Perdigó n et al, 1998;Valdez et al, 1997). However, we cannot ignore the possibility that the intestinal inflammatory process preceding tumour development may be due to change in the epithelial cell induced by the carcinogen which enters the intestine as glucuronide, and where the normal microflora has the important role of deconjugating this compound by enzymes synthesized by gut microorganisms.…”
Section: Yoghurt As Immunomodulator In Colon Cancer Preventionmentioning
confidence: 99%
“…We observed that yoghurt supplements every 10 days for 6 months inhibited tumour development. We suggested that one of the mechanisms by which yoghurt exerts antitumour activity is through its immunomodulatory response mediated by a severe reduction (down regulation) of the inflammatory response induced by the carcinogen (Perdigó n et al, 1998;Valdez et al, 1997). However, we cannot ignore the possibility that the intestinal inflammatory process preceding tumour development may be due to change in the epithelial cell induced by the carcinogen which enters the intestine as glucuronide, and where the normal microflora has the important role of deconjugating this compound by enzymes synthesized by gut microorganisms.…”
Section: Yoghurt As Immunomodulator In Colon Cancer Preventionmentioning
confidence: 99%
“…In week 8, yogurt or supernatant were again added to the diet for 10 consecutive days. This procedure was repeated every 10 days during the 16 weeks of experimentation, according to a previous study (3). The animals were housed individually and the amount of yogurt ingested was between 2,5 to 3 mild.…”
Section: Tumor Induction and Feeding Proceduresmentioning
confidence: 99%
“…We also determined that yogurt inhibited an experimental intestinal tumor induced by the carcinogen 1,2 dimethylhidrazine (DMH) in BALB/c mice. We suggested that one of the mechanisms by which yogurt inhibits the establishment and growth of the tumor could be through a down regulation in the inflammatory immune response (3). Macrophages are also involved in the inhibition of tumor.…”
mentioning
confidence: 99%
“…There have been numerous reports on the potentially beneficial effects of consumption of yoghurt and dairy products containing lactic acid bacteria by either patients with allergic diseases (Wheeler et al, 1997a,b;Van de Water et al, 1999) healthy volunteers (Arunachalam et al, 2000;Chen et al, 1999;Halpern et al, 1991;Yoon et al, 1999;Solis-Pereyra et al, 1997) and laboratory animals (Solis Pereyra et al, 1997;Perdigon et al, 1998;Ha et al, 1999).…”
Section: Introductionmentioning
confidence: 99%